Patients’ Attitudes and Experiences of Disease‐Modifying Antirheumatic Drugs in Rheumatoid Arthritis and Spondyloarthritis: A Qualitative Synthesis - Kelly, Ayano (Arthritis Care Res (Hoboken), 2018)
OBJECTIVE: Nonadherence to disease‐modifying antirheumatic drugs (DMARDS) in rheumatoid arthritis (RA) and spondyloarthritis (SpA) results in increased disease activity and symptoms and poorer quality of life. We aimed to describe patients’ attitudes and experiences of DMARDs in RA and SpA to inform strategies to improve medication adherence. METHODS: Databases (MEDLINE, Embase, PsycINFO, and CINAHL) were searched to January 2016. Thematic synthesis was used to analyze the findings. RESULTS: From 56 studies involving 1,383 adult patients (RA [n = 1,149], SpA [n = 191], not specified [n = 43]), we identified 6 themes (with subthemes): intensifying disease identity (severity of sudden pharmacotherapy, signifying deteriorating health, daunting lifelong therapy), distressing uncertainties and consequences (poisoning the body, doubting efficacy, conflicting and confusing advice, prognostic uncertainty with changing treatment regimens), powerful social influences (swayed by others’ experiences, partnering with physicians, maintaining roles, confidence in comprehensive and ongoing care, valuing peer support), privilege and right of access to biologic agents (expensive medications must be better, right to receive a biologic agent, fearing dispossession), maintaining control (complete ownership of decision, taking extreme risks, minimizing lifestyle intrusion), and negotiating treatment expectations (miraculous recovery, mediocre benefit, reaching the end of the line). CONCLUSION: Patients perceive DMARDs as strong medications with alarming side effects that intensify their disease identity. Trust and confidence in medical care, positive experiences with DMARDS among other patients, and an expectation that medications will help maintain participation in life can motivate patients to use DMARDs. Creating a supportive environment for patients to voice their concerns may improve treatment satisfaction, adherence, and health outcomes.